Factor influencing the intention to use E-Commerce among generation-y in Kota Bharu - Azila Anuar; Darshini Ravintharan; Mohamad Ameer Hafies Rosli; Ng Chai Xuan (2023)
The purpose of this research is to determine what factors entice generation y in Kota Bharu to use internet banking for online purchases. Intention to use online banking purpose was found to be a dependent variable after five independent variables were analysed: perceived security, perceived usefulness, perceived ease of use, consumer trust, and malware attack. A few variables from the Technology Acceptance Model (TAM) were employed to examine the intention to use online banking of ecommerce users. The term "online banking intention" refers to a person's plan to use their payment method to pay for a product or service. Therefore, it's important to look into the role that these six dimensions play in shaping e-commerce consumers' intentions when it comes to online banking. In recent years, e-commerce in Malaysia has expanded rapidly. For online stores to succeed, they need to differentiate themselves from the competition by increasing their customers' propensity to make a purchase. The information for this study was gathered from the 380 respondents of Kota Bharu who took part in online surveys about their online banking services. For the statistical analysis, we used Statistical Package for Social Science (SPSS) version 26.0. As a result, the study relies on Pearson's correlation analysis. Therefore, it is recommended that e-commerce platforms use appropriate specific ways to strengthen those parts and the online banking purpose.